Severity of multisystem inflammatory syndrome in children (MIS‐C) in patients with and without mucocutaneous findings. Issue 2 (10th January 2023) - Rao, Megana; Bond, Caitlin; Haggstrom, Anita; Bhumbra, Samina
Abstract: Background: There are few studies comparing severity of MIS‐C disease with mucocutaneous symptoms, age, race, and ethnicity. Objective: To describe the mucocutaneous symptoms present on admission and evaluate whether these symptoms are correlated with a more severe MIS‐C disease course. Methods: Retrospective cohort study of hospitalized patients with suspected MIS‐C between May 13, 2020 to April 21, 2021. Results: Of the 66 patients who met the inclusion criteria, 84.8% (56/66) exhibited mucocutaneous findings. The most common mucocutaneous symptoms were rash, conjunctivitis, cracked lips, and sore throat. Children with mucocutaneous symptoms were younger (median 9.8 years) compared to those without (11.4 years), p = .39. The groups had similar proportions of pediatric intensive care unit admission, abnormal cardiology studies, and necessity of pressors. The presence of mucocutaneous findings on admission was associated with a lower troponin level on admission (median 0.08 ng/ml vs. 0.52, p = .003). Black children had higher odds of severe MIS‐C compared to White children (odds ratio [95% CI]: 3.30 [1.02, 10.72], p = .047). Children ≥5 years of age had greater odds of severe MIS‐C compared to children <5 years of age (odds ratio [95% CI]: 5.43 [1.39, 21.23], p = .02). Limitations: The sample size was relatively small, there was no dermatologist present on admission, initial diagnostic testing and management varied if patients presented at outside hospitals, and the CDC case definition for MIS‐C was highly sensitive. Conclusion: The presence of mucocutaneous symptoms negatively correlated with troponin levels, but there was no significant association between these symptoms and other markers of cardiac involvement (echocardiogram, ejection fraction, electrocardiogram).